Challenges Faced by Caregivers and their Influence on the Patients' Health Recovery Process at Mulago National Referral Hospital - Anitah Orishaba (Uganda Christian University, 2025)
The research was about “Challenges Faced By Caregivers and their influence on Patients’ health recovery process At Mulago National Referral Hospital”. The goal of the study was to highlight the challenges faced by Mulago National Referral Hospital patients and caregivers in order to provide viable alternatives for maximizing the caregiving resources available in Ugandan healthcare institutions. The cross-sectional research approach used during the study enabled the researcher to analyze the challenges faced by Mulago National Referal Hospital patients and caregivers. In this inquiry, the researcher used purposeful sampling. This is because the cross-sectional nature of the study required specificity in the selection of sample elementsStatistics gathered from the sampled caregivers at Mulago National Referral Hospital indicated that the problems pointed out by previous study findings still apply in the current situation. The results of this investigation indicated that caregivers encountered a variety of challenges, including the incapacity to care for patients and earn a living at the same time, the time commitment involved in providing care, the risk of depression and stress, the inability to get enough sleep while giving care, the frequency of financial issues related to providing care among others. Overall, the study's insights captured the actual circumstances that caregivers face when tending to patients or loved ones. That is, caregivers face a number of difficulties, including the inability to provide care for patients and earn a living at the same time, the time commitment of caregiving, the associated stress and depression, the inability to get enough sleep during caregiving, the frequent occurrence of financial difficulties related to caregiving among others. The study recommended the need for additional research on health insurance schemes. More research is required on the fundamental health curriculum and training paradigm for the general public. It is necessary to implement a fundamental health and first aid knowledge education model and methods of delivery because everyone has the potential to provide healthcare, whether at a medical facility or even at home.
THESIS